2017
DOI: 10.1002/app.45531
|View full text |Cite
|
Sign up to set email alerts
|

Solution self‐assembly behavior of ABC triblock polymers and the implications for nanoporous membrane fabrication

Abstract: Self‐assembled block polymer membranes are rising to the fore of next‐generation separations technologies, and a particular fabrication process of significant interest is the self‐assembly and non‐solvent induced phase‐separation (SNIPS) method. This is because the SNIPS process allows for the facile manipulation of independent variables to produce simultaneously size‐ and chemically‐selective membranes in a scalable manner. Despite significant advances in the SNIPS membrane fabrication procedure, the early‐st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…The differences in mechanical strength development reported in Figure 5 at the same polymer concentration may be attributed to the possible long-range lattice organization based on the differences in block chemistry of each sample. Sargent, et al 7 previously reported that ISD terpolymer solutions (59 kg mol -1 ) formed individual micelles at low polymer concentrations (<1 wt.%) and long-range lattices at significantly higher polymer concentration (>22 wt.%) using DOX as solvent. Dorin, et al 2 showed that 16 wt.% ISV terpolymer solutions (59 kg mol -1 ) organized into lattices using a 7:3 THF:DOX solvent mixture.…”
Section: Viscoelastic Behavior With Significant Evaporationmentioning
confidence: 99%
See 3 more Smart Citations
“…The differences in mechanical strength development reported in Figure 5 at the same polymer concentration may be attributed to the possible long-range lattice organization based on the differences in block chemistry of each sample. Sargent, et al 7 previously reported that ISD terpolymer solutions (59 kg mol -1 ) formed individual micelles at low polymer concentrations (<1 wt.%) and long-range lattices at significantly higher polymer concentration (>22 wt.%) using DOX as solvent. Dorin, et al 2 showed that 16 wt.% ISV terpolymer solutions (59 kg mol -1 ) organized into lattices using a 7:3 THF:DOX solvent mixture.…”
Section: Viscoelastic Behavior With Significant Evaporationmentioning
confidence: 99%
“…6 7 8 9 The high solute selectivity as well as the high solvent permeability are key properties of SNIPS membranes that are the direct result of the high density of uniform pores obtained by the assembly of block copolymers. 7 A SNIPS membrane is comprised of a hierarchical tapered structure. 10 The selective layer is the result of block copolymer assembly and exhibits a well-ordered structure with a high density of uniform nanoscale pores, the main function of which is to separate solutes from the solvent.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The evaporation of solvent generates an increased polymer concentration at the solution-air interface, which causes the block polymer to form into ordered nanostructures across the top surface of the film. 56,[58][59][60][61] At this juncture, it is critical to note that these nanostructures are dynamic and driving toward equilibrium such that the instantaneous nanostructure observed at any point during the evaporation step depends upon the solution composition, solvent evaporation rate, and block polymer properties. At the end of the solvent evaporation step, the film is plunged into a non-solvent bath.…”
Section: Introductionmentioning
confidence: 99%